2015
DOI: 10.1007/s11999-015-4226-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Outcomes of Bridge-enhanced Anterior Cruciate Ligament Repair Are Influenced by Sex in a Preclinical Model

Abstract: The current findings highlight the critical role of sex on the biomechanical outcomes of bridge-enhanced ACL repair in a relevant large animal model. Better understanding of the mechanisms responsible for these observations using preclinical models and concomitant clinical studies in human patients may allow for additional development of sex-specific surgical and rehabilitative strategies with potentially improved outcomes in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…The 4.5-mm femoral and tibial tunnels were then drilled slightly anterior to the ACL footprint on the femoral attachment and slightly posterior to the tibial attachment to protect the native ACL insertion sites. 27 , 40 An Endobutton (Smith & Nephew) carrying 3 looped sutures was passed through the femoral tunnel and flipped to engage the cortex. Two sutures were threaded through the scaffold, and the scaffold was introduced into the notch until femoral contact was visually verified.…”
Section: Methodsmentioning
confidence: 99%
“…The 4.5-mm femoral and tibial tunnels were then drilled slightly anterior to the ACL footprint on the femoral attachment and slightly posterior to the tibial attachment to protect the native ACL insertion sites. 27 , 40 An Endobutton (Smith & Nephew) carrying 3 looped sutures was passed through the femoral tunnel and flipped to engage the cortex. Two sutures were threaded through the scaffold, and the scaffold was introduced into the notch until femoral contact was visually verified.…”
Section: Methodsmentioning
confidence: 99%
“… 19 The other one compared the HRT and conservative treatment. 17 Of the 11 animal studies, six compared bio-enhanced ACL repair and suture repair only, 1 , 21 , 22 , 23 , 24 , 25 , 26 one compared bio-enhanced repair with ACL reconstruction, 27 and compared the outcome of bio-enhanced ACL repair with different fixation methods, 28 platelet-rich plasma (PRP) injection temperature, 29 concentration of PRP 30 and time of delay. 31
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“… Nguyen et al. 21 10 goats Locking suture technique with and without SIS vs intact control 12 wk The cross-sectional area of two suture groups was 35% and 50% of the intact control, respectively. Suture-SIS group showed mechanical improvement than the Suture group at 30°.…”
Section: Resultsmentioning
confidence: 99%
“…Only recently, primary ACL repair has regained increasing research interest. A number of preclinical studies demonstrated the potential role of primary repair in combination with modern surgical techniques and enhancing bioactive materials 7,[11][12][13] . Taylor et al mentioned that despite the reported unacceptable high failure rates of previously published clinical studies, there constantly was a subset of patients that met the criteria for clinical success 14 .…”
Section: Introductionmentioning
confidence: 99%